INITIAL RESULTS OF THE RE-VERSE AD TRIAL: IDARUCIZUMAB REVERSES THE ANTICOAGULANT EFFECTS OF DABIGATRAN IN PATIENTS IN AN EMERGENCY SETTING OF MAJOR BLEEDING, URGENT SURGERY OR INTERVENTIONS. Issue 12 (23rd November 2015) - Pollack, C; Eikelboom, J; Weitz, J; Reilly, P; Glund, S; Dubiel, R; Kreuzer, J; Stangier, J; Wang, B; Gagg, J; Verhamme, P; Bernstein, R; et al.
Abstract : Objectives & Background: Dabigatran, an oral thrombin inhibitor, is widely used for stroke prevention in atrial fibrillation. Idarucizumab, a monoclonal antibody fragment directed against dabigatran, demonstrated immediate, complete and sustained reversal of the anticoagulant effect of dabigatran, without procoagulant activity, in animal models and human volunteers. Aims To examine the efficacy and safety of idarucizumab to rapidly reverse the anticoagulation effects of dabigatran in critical clinical situations. Methods: RE-VERSE AD is an ongoing multinational, open-label, single cohort study with a target size of up to 300 patients. It is designed to study the reversal of dabigatran's anticoagulant effect by 5 g idarucizumab given as two 2.5 g IV bolus infusions, in patients who experience life-threatening or uncontrollable bleeding (Group A) or who require emergency surgery or invasive procedure (Group B). The primary endpoint is the maximum reversal of the anticoagulant effect of dabigatran, based on central laboratory determination of the dilute thrombin time or ecarin clot time up to 4 hours after idarucizumab administration. Drug levels and other measures of dabigatran activity are also determined. Clinical outcomes, including cessation of bleeding, thrombotic events, and other safety measures, are assessed. Results: In the first 90 patients, idarucizumab normalized clotting tests in at least 90% of patients, an effect evident at the first measurement. There was one thrombotic event within 72 hours of idarucizumab administration in a patient whose anticoagulant therapy had not been restarted. Conclusion: Idarucizumab is a promising specific reversal agent that rapidly and safely reverses dabigatran's anticoagulant effects within minutes in emergency situations that reflect real world clinical practice.